Características agronômicas, produtividade e qualidade fisiológica da soja safrinha sob semeadura direta, em função da cobertura vegetal e da calagem superficial - Lima, Eduardo do Valle; Crusciol, Carlos Alexandre Costa [UNESP]; Cavariani, Cláudio [UNESP]; Nakagawa, João [UNESP] (My University, 2009)
Soybean productivity under the no till system (NTS) can be influenced by the preceding type of plant cover and surface liming. However, the effects of this technique on yield components and the seed physiological quality have been little studied, especially in (safrinha) off-season soybean under NTS. Therefore, this study aimed to evaluate some agronomic traits, yield components, productivity, and physiological quality of soybean grown during the off-season (safrinha), as a function of different cover plants, with or without surface liming, under NTS. The experiment was conducted during the 1999/00 cropping season on the Lageado Experimental Farm, FCA/UNESP/Botucatu-SP, Brazil. The experimental design was organized as randomized blocks in split-plots, with 4 replications. The 6m × 10m plots consisted of broomcorn (Sorghum bicolor), millet (Pennisetum americanum), fall panicum (Panicum dichotomiflorum), spontaneous vegetation, and no vegetation. At 53 days after emergence the cover plants were desiccated and lodged, and a surface application of 3.1 t.ha-1 lime was made in half of the plots, in order to increase V% to 70. Soybean (cv. IAC-19) was sown two weeks later, during the off-season (safrinha). Determinations were made for the final stand, first pod height, plant height, total number of pods and blank pods per plant, total number of seeds per pod, 100-seed weight and yield. As to seed physiological quality, determinations were made for germination, artificial aging, germination at 18°C, plantlet D.M., and electric conductivity. During NTS implementation, plant cover type and surface liming did not affect the agronomic traits studied, yield components, seed productivity, and physiological quality of soybean seeds grown in the off-season (safrinha) system, except for electric conductivity.
Agronomic traits, yield and physiological quality of safrinha (off-season) soybean under no till as a function of plant cover and surface liming
Keywords: Cover plant; Glycine max; Seed; Yield components